2011
DOI: 10.1109/tbme.2010.2071871
|View full text |Cite
|
Sign up to set email alerts
|

Extended Noninvasive Fetal Monitoring by Detailed Analysis of Data Measured With Phonocardiography

Abstract: This paper presents a complex heuristic method for the evaluation of fetal heart sounds, applying simultaneously several algorithms, where the autocorrelation technique has been completed with the wavelet transform and the matching pursuit methods. In this way, a more reliable heart rate variability can be achieved and further parameters of the cardiac operation can be assessed in addition to the conventional cardiotocographic examination. This also comprises those parameters, which can be investigated only wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 21 publications
0
23
0
6
Order By: Relevance
“…However, these fPCG signals are heavily contaminated by noise from various sources [611]. Hence to extract important diagnostic information such as FHR, frequency/pitch, intensity, timing, and energy of fetal heart sound, this technique requires matured signal processing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…However, these fPCG signals are heavily contaminated by noise from various sources [611]. Hence to extract important diagnostic information such as FHR, frequency/pitch, intensity, timing, and energy of fetal heart sound, this technique requires matured signal processing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A publication by Kovcs, Ferenc et al [9] presents a complex heuristic method for the evaluation of fetal heart sounds, applying simultaneously several algorithms, where the autocorrelation technique has been completed with the wavelet transform and the matching pursuit methods. In this way, a more reliable heart rate variability can be achieved and further parameters of the cardiac operation can be assessed in addition to the conventional cardiotocographic examination.…”
Section: Related Workmentioning
confidence: 99%
“…Kalman filtering (Adithya et al, 2017) needs accurate reference signal, as it has high computational complexity. Wavelet Transform (Kosa et al, 2008; Kovacs et al, 2011; Fodor et al, 2012; Adithya et al, 2017; Koutsiana et al, 2017), showed good performance in de-nosing noisy fPCG and analyzing the fetal heart sounds (fHS), but it lacks the ability to finely de-noise the overlapped frequency components. Independent Component Analysis (ICA) (Nigam and Priemer, 2004; Jimenez-Gonzalez and James, 2008; Jiménez-Gonzàlez and James, 2010; Jimenez and James, 2013) assumes source components as independent (which is hardly met in case of abdominal sources of sounds) and needs post processing with high computational complexity.…”
Section: Introductionmentioning
confidence: 99%